PEMBERDAYAAN YURISPRUDENSI SEBAGAI HUKUM ISLAM (Analisis Fungsional dalam Rangka Optimalisasi Kinerja Hakim Agama) - Andi Jasmani (Al-Bayyinah, 2017)
AbstractReligion judge is one of human service for justice seeker through religion judicature. These is one principle that religion judge as other judges cannot refuse lawsuit with unarranged reason by the law.In doing the principle above, jurisdiction has an important role. This is caused by the cases which have the similarities. The fact shows that the laws cannot cover all cases well because of article faktor which is interpretative or the case is new one from this fact, religion judge has to have broad knowledge about jurisdiction. Thats the cause that jurisdiction is admitted as one of the important law source in judicature world.Kata Kunci: Yurisprudensi, Hakim Agama, Pemberdayaan, Analisis Fungsional.